The Ever Widening Gyre: Factors Affecting Change in Adult Education Graduate Programs - Judy Milton; Watkins; Spears Karen; Scarlette Studdard; Michele Burch (Adult Education Research Conference, 2000)
The purpose of this survey study was to understand the factors that have influenced recent changes in the size of adult education graduate programs. We found that integration has a significant effect on changes in student enrollment while leadership, innovation, and integration all significantly predict variance in faculty growth.